Persons who may act as attorney and grounds for impeachment of the attorney - Smolichki, Pavel (Law Journal of New Bulgarian University, 2023)
The judicial system is called upon to ensure the resolution of conflicts in society. The results of this system depend to a large extent on the effective participation of citizens defending their personal rights and interests in specific cases. At the same time, the constant development of society requires the evolution of its most important social regulator – the law, whose changes quite naturally affect the functioning of the judicial system itself. This leads to the conclusion that a good knowledge of the ever-changing legal framework is a prerequisite for citizens’ full participation in the process. The institution of the attorney has long existed in Bulgarian criminal procedure and has been adopted from Russian law. However, it is a subject of relatively low research interest. This could be explained, on the one hand, by the fact that the attorney performs an auxiliary role in the performance of functions in criminal proceedings. Also, the participation of the attorney in the criminal proceedings in a large number of cases is related to the implementation of additional, atypical functions for the criminal proceedings – those of bringing and substantiating the civil action and its defence. However, the very fact of its invariable existence throughout the history of our criminal procedure law is indicative of its essential role in achieving the objectives of the state’s criminal policy and ensuring the public interest in this respect. The present study identifies the persons who may be attorneys under Bulgarian criminal procedure law. The grounds for dismissal of the attorney are also examined.